Dynamic identification in VARs - Paul Beaudry; Fabrice Collard; Patrick Fève; Alain Guay; Franck Portier (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2022)
Most macroeconomic models, both fully structural models as well as SVAR models, view economic outcomes as the product of a combination of endogenous and exogenous dynamic forces. In particular, the exogenous forces are generally modeled as a set of linearly independent dynamics processes. In this paper we begin by showing that this dual dynamic structure is sufficient to identify the entire set of structural impulse responses inherent to any such model. No extra restrictions are necessary. We then use this observation to suggest how it can be used to evaluate common SVAR restrictions (impact restrictions, long-run restrictions and proxy-VAR), as well as help transpire the role of cross-equation restrictions inherent to more structural models.
Keywords: C32; E32; 330; Structural Shocks; Dynamic Identification; SVARs; DSGE models